Sultan To Launch UPM College's Anniversary Do - The Star (2008)
The Sultan of Selangor Sultan Sharafuddin Idris Shah will launch the 25th anniversary celebrations of Universiti Putra Malaysia s Sultan Alaeddin Suleiman Shah College.